Structural requirements of acetylcholinesterase reactivators - Kuca, Kamil; Juna, Daniel; Musilek, Kamil (Mini reviews in medicinal chemistry, 2006)
Nerve agents (sarin, soman, cyclosarin, tabun and VX agent) and pesticides (paraoxon, chlorpyrifos, TEPP) represent extremely toxic group of organophosphorus compounds (OPCs). These compounds inhibit enzyme acetylcholinesterase (AChE, EC 3.1.1.7) via its phosphorylation or phosphonylation at the serine hydroxy group in its active site. Afterwards, AChE is not able to serve its physiological function and intoxicated organism is died due to overstimulation of cholinergic nervous system. The current standard treatment of poisoning with highly toxic OPCs usually consists of the combined administration of anticholinergic drugs (preferably atropine) and AChE reactivators (called "oximes"). Anticholinergic drugs block effects of accumulated neurotransmitter acetylcholine at nicotinic and muscarinic receptor sites, while oximes reactivate AChE inhibited by OPCs. Unfortunately, none from the currently used oximes is sufficiently effective against all known nerve agents and pesticides. Therefore, to find new oximes able to sufficiently reactivate inhibited AChE (regardless of the type of OPCs) is still very important task for medicinal chemistry with the aim to improve the efficacy of antidotal treatment of the acute poisonings mentioned. In this paper, the relationship between chemical structure of AChE reactivators and their ability to reactivate AChE inhibited by several nerve agents and pesticides is summarized. It is shown that there are several structural fragments possibly involving in the structure of proposed AChE reactivators. Finally, an attempt of a future course of new AChE reactivators development is discussed.
Keywords: receptor muskarinový M1; fosforylace; Phosphorylation; acetylcholinesterasa; cholinesterasové inhibitory; antidota; Acetylcholinesterase; aktivace enzymů; Enzyme Activation; Animals; Cholinesterase Reactivators; acetylcholin; neurotransmiterové látky; Neurotransmitter Agents; Humans; reaktivátory cholinesterasy; Receptor, Muscarinic M1; Chemical Warfare Agents; antagonisté muskarinových receptorů; Acetylcholine; oximy; vazebná místa; chemické bojové látky; atropin; Atropine; Cholinesterase Inhibitors; zvířata; Binding Sites; Oximes; nikotin; lidé; Nicotine; Muscarinic Antagonists; Antidotes